Heavy metal deposition through rainfall in Chinese natural terrestrial ecosystems: Evidences from national-scale network monitoring. (December 2016) - Zhu, Jianxing; Wang, Qiufeng; Yu, Haili; Li, Meiling; He, Nianpeng
Abstract: Industrialization and urbanization have led to increasingly serious levels of atmospheric heavy metal pollution, which is one of the main sources of heavy metals to terrestrial ecosystems. Therefore, it is essential to quantify atmospheric fluxes and explore their potential effects on natural ecosystems and human welfare. We monitored water-soluble heavy metals (lead (Pb), cadmium (Cd), and chromium (Cr)) in rainfalls on a monthly basis in 2013 and 2014, at 31 field stations located in typical natural Chinese ecosystems. The average soluble Pb, Cd, and Cr deposition was 1.90 ± 1.54, 0.28 ± 0.25, and 0.96 ± 0.48 mg m −2 yr −1, respectively, with a large variation among the different sites. Generally, the atmospheric deposition of soluble Pb, Cd, and Cr was higher in the southwest, central, south, and north China than in the northwest and northeast China, Inner Mongolia, and Qinghai-Tibet. As expected, the atmospheric heavy soluble metal deposition fluxes were significantly correlated with the number of vehicles ( Ps < 0.1). The wet deposition of soluble Pb and Cr was positively correlated with oil and coal consumption, unlike Cd deposition. Moreover, soluble Pb and Cd in atmospheric wet deposition were positively correlated with the contents of Pb and Cd in soil at different regions. In this study, atmospheric heavy metal deposition through rainfall in typical natural ecosystems in China is assessed at the national scale, alerting potential ecological hazards resulting from an increasing atmospheric heavy metal deposition and providing a basis for future studies. Highlights: Investigating heavy metal deposition through rainfall in Chinese natural ecosystem. Precipitation, vehicles number, energy consumption affect heavy metal deposition. Wet heavy metals deposition was positive correlated with soil metals contents. Increasing heavy metals deposition have adverse effects on natural ecosystem.